A Statistical Analysis of the Energy Dissipation Rate Estimated From the PMWE Spectral Width in the Antarctic. Issue 16 (13th August 2020) - Kohma, M.; Sato, K.; Nishimura, K.; Tsutsumi, M.; Sato, T.
Abstract: The radar volume reflectivity and turbulent kinetic energy dissipation rate in the Antarctic mesosphere were estimated from the polar mesosphere winter echoes (PMWE) recorded using a vertical beam of the PANSY radar, a Mesosphere‐Stratosphere‐Troposphere radar at Syowa Station (69°S, 40°E), over a period of 4 years. The observed radar volume reflectivity exhibits a lognormal distribution in the range of 2 × 10 −18 to 5 × 10 −15  m −1 for a height region of 55–82 km. The turbulent energy dissipation rate estimated from the spectral widths of the PMWE ranges from 10 −4 to 10 0  m 2  s −3 . From monthly histograms of the turbulent energy dissipation rate for a fixed solar zenith angle (SZA) and height, it was found that the summer‐to‐winter transition of the turbulent energy dissipation rate occurs in March, while the winter‐to‐summer transition occurs in September. This seasonal variation agrees well with that of gravity wave activity, suggesting that the turbulence in the mesosphere is likely caused by gravity wave breaking. Key Points: The turbulent kinetic energy dissipation rates in the Antarctic mesosphere from PMWE spectral widths are estimated The dissipation rates at heights of 55–82 km are in the range of 10 –4 to 10 0  m 2  s –3 The summer‐to‐winter (winter‐to‐summer) transition of the turbulence parameters occurs in April (September)